Efektivitas Implementasi Program Pilar Indobara untuk Peningkatan Kinerja SHE di PT Putra Perkasa Abadi Jobsite Borneo Indobara - Muhammad Osaegi Restu Amrulloh; Rochmad Choirul Muachor; Zinedina Salsabila Mustain (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The mining sector in Indonesia inherently involves high OSH (Occupational Safety and Health) and Environmental risks, necessitating strict adherence to regulations like Ministerial Decree of Energy and Mineral Resources No. 1827/2018 and Directorate General of Mineral and Coal Decree No. 185/2019. PT Putra Perkasa Abadi (PPA) at the Borneo Indobara Site launched the Indobara Pillar Program to optimize SHE (Safety, Health, Environment) performance and achieve